Patterns of Neglect Dissociation - Cristina Barbieri; Ennio De Renzi (Behavioural Neurology)
Extinction in the visual, tactile and auditory modality, and visual, tactile and motor neglect were investigated in 40 right brain-damaged (RBD) and 50 left brain-damaged (LBD) patients. The presence of neglect was assessed with reference to the performance of 50 control patients. Visual neglect was only found in RBD patients and its severity could vary from one test to another. Tactile neglect was much rarer and it occurred with lesions in either hemisphere. Five cases of motor neglect were found in patients with right parietal damage. Both extinction and neglect could be present either confined to I modality or involving 2 or more. The assumption that extinction always represents an attenuated form of neglect was challenged by the finding of 1 patient with visual neglect but no visual extinction and of3 patients with extinction in all modalities and no sign of neglect. Exploration of contralateral space would appear to be a process monitored by mechanisms decentralized at the level of the single modality rather than by a supramodal supervisor.